Parent Responses to Pediatric Headache - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Parent and child report measures of the frequency and quality of parent responses to children's recurrent headache were evaluated for 153 pediatric patients at the University of Maryland School of Medicine, Baltimore, using a 16-item scale modeled after part II of the West Haven-Yale Multidimensional Pain Inventory, which assesses patients' perceptions of others' responses to pain, and a Child Behavior Checklist, to assess parent perceptions of the child's behavioral responses.